The system of tactical training basketball teams of students using interactive technologies. - Kozina Zh.L; Kondak N.N; Koval M.V; Paschenko N.A; Kіrsanov N.V (Kharkov National Pedagogical University, 2011)
A program for improving the effectiveness of tactical training of basketball teams of students with techniques to enhance the perception of figurative elements of technique and tactics of basketball on the basis of modern information technology. The study involved 23 female basketball players of 18-23 years of student teams, 11 of which were experimental group and 12 - control. Established that the developed system improves the quality of performance technique techniques of basketball, the effectiveness of actions in the game, raising the number of implemented in-game tactical interactions.